IPEM code of practice for high-energy photon therapy dosimetry based on the NPL absorbed dose calibration service. (21st September 2020) - Eaton, David J; Bass, Graham; Booker, Paul; Byrne, John; Duane, Simon; Frame, John; Grattan, Mark; Thomas, Russell AS; Thorp, Natalie; Nisbet, Andrew
Abstract: The 1990 code of practice (COP), produced by the IPSM (now the Institute of Physics and Engineering in Medicine, IPEM) and the UK National Physical Laboratory (NPL), gave instructions for determining absorbed dose to water for megavoltage photon (MV) radiotherapy beams (Lillicrap et al 1990 ). The simplicity and clarity of the 1990 COP led to widespread uptake and high levels of consistency in external dosimetry audits. An addendum was published in 2014 to include the non-conventional conditions in Tomotherapy units. However, the 1990 COP lacked detailed recommendations for calibration conditions, and the corresponding nomenclature, to account for modern treatment units with different reference fields, including small fields as described in IAEA TRS483 (International Atomic Energy Agency (IAEA) 2017, Vienna). This updated COP recommends the irradiation geometries, the choice of ionisation chambers, appropriate correction factors and the derivation of absorbed dose to water calibration coefficients, for carrying out reference dosimetry measurements on MV external beam radiotherapy machines. It also includes worked examples of application to different conditions. The strengths of the 1990 COP are retained: recommending the NPL2611 chamber type as secondary standard; the use of tissue phantom ratio (TPR) as the beam quality specifier; and NPL-provided direct calibration coefficients for the user's chamber in a range of beam qualities similar to those in clinical use. In addition, the formalism is now extended to units that cannot achieve the standard reference field size of 10 cm × 10 cm, and recommendations are given for measuring dose in non-reference conditions. This COP is designed around the service that NPL provides and thus it does not require the range of different options presented in TRS483, such as generic correction factors for beam quality. This approach results in a significantly simpler, more concise and easier to follow protocol.